The Influence of Satisfaction and Trust on Sympathy Card Customer Loyalty in Students of the Faculty of Economics and Business UPN Veteran East Java - Ardianta, Armanda; Purwanto, Sugeng (East Asian Journal of Multidisciplinary Research, 2024)
Business competition in the development of the current era of globalization makes companies have to quickly think hard about how to behave and act effectively and efficiently, especially when facing competition in a business environment that moves very fast and keeps up with the times and is full of uncertainty. Therefore, every company is required to compete competitively in terms of creating and maintaining loyal customers. This study aims to analyze customer loyalty by looking at the effect of satisfaction and trust whether it can influence customer loyalty sympathy on students of the Faculty of Economics and Business UPN "Veteran" East Java. The population in this study were students of the Faculty of Economics and Business UPN "Veteran" East Java, class of 2019 - 2022. The sampling technique used was convenience. with 100 respondents who were determined as a sample. The questionnaire method is a method for collecting data in this study. This research data analysis technique uses Partial Least Square (PLS). The results showed that satisfaction and trust have a significant effect on customer loyalty. This can be interpreted that increasing customer satisfaction and trust will also increase loyalty to students of the Faculty of Economics and Business UPN Veteran East Java as customers of the sympathy card.